2017
DOI: 10.17265/1934-7391/2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Photogem® (Hematoporphyrin Derivative) as a Photoactivatable Larvicide against Aedes aegypti (Diptera: Culicidae) Larvae

Abstract: Dengue vector is responsible for millions of deaths every year and has caused disastrous impacts on health systems. The continuous use of chemical insecticides, such as carbamates, pyrethroids and organophosphates generates resistant populations of the mosquito, therefore, new control methods must be investigated. The joint action of the population and guidelines for preventing the reproduction of the mosquito associated with the use of photoactivatable insecticides can be the alternative for the control of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In 2017, Souza et al [74] (Entry 7, table 2) evaluated the photolarvicidal efficiency of Photogem ® (PG), a HP derivative, was evaluated in 2nd and 3rd instar larvae of A. aegypti (Diptera: Culicidae) under artificial lighting with fluorescent lamps and sunlight . The authors observed mortality rates of 71, 91 and 100% for PG in aqueous medium at concentrations of 20, 40 and 80 µg ml −1 , respectively, incubated for 12 h and exposed to the sun in the intensity range of 30-60 mW cm −2 .…”
Section: Vdbsmentioning
confidence: 99%
“…In 2017, Souza et al [74] (Entry 7, table 2) evaluated the photolarvicidal efficiency of Photogem ® (PG), a HP derivative, was evaluated in 2nd and 3rd instar larvae of A. aegypti (Diptera: Culicidae) under artificial lighting with fluorescent lamps and sunlight . The authors observed mortality rates of 71, 91 and 100% for PG in aqueous medium at concentrations of 20, 40 and 80 µg ml −1 , respectively, incubated for 12 h and exposed to the sun in the intensity range of 30-60 mW cm −2 .…”
Section: Vdbsmentioning
confidence: 99%
“…In Nigeria, it is estimated that 80 to 120 million people are at risk of the disease (Hotez et al, 2012). Viral encephalitis is an inflammation of the brain parenchyma that is indicated by fever, headache and in extreme cases, seizures (fits), confusion, drowsiness, and loss of consciousness, and even coma (Saema & Michael, 2020). The West Nile Fever is a flavivirus (a group of single stranded RNA viruses that cause severe endemic infections and epidemics on a global scale) that has similarities with the viruses that cause St. Louis encephalitis, Japanese encephalitis, and yellow fever and infects humans, horses, and a variety of bird species.…”
Section: Introductionmentioning
confidence: 99%